PARTISIPASI PEMILIH PEMULA PADA PEMILIHAN KEPALA DESA BENTARSARI KECAMATAN SALEM KABUPATEN BREBES TAHUN 2022 - Maulana , Sofyan Fikri; Nurwanda , Asep; Garis , Regi Refian (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
This research is motivated by the phenomenon of low participation of new voters in the Village Head Election in Bentarsari, Salem District, Brebes Regency. Although new voters have the potential to have a significant impact on the local democratic process, in reality they are often not actively involved. This can be caused by various factors, including a lack of understanding of the election process, dissatisfaction with candidates, and minimal socialization carried out by related parties. The method used in this study is a qualitative method, which aims to dig up in-depth information about the participation of new voters. Through interviews and focus group discussions, this study seeks to understand the perspectives and experiences of new voters in the context of the village head election. The main focus of the study is to identify the factors that influence their participation, as well as how efforts can be made to increase their involvement in the election process. The results of this study are expected to provide a clearer picture of the challenges faced by new voters and possible solutions. By understanding the reasons behind the low participation, stakeholders, including village governments and community organizations, can design more effective strategies to increase awareness and involvement of new voters. Overall, this study is expected to contribute to the literature on political participation, especially among first-time voters, as well as provide practical recommendations to increase participation in future village head elections. Thus, this study is not only relevant for academics, but also for practitioners involved in the election process and community development